SISTEM PENDUKUNG KEPUTUSAN PENENTUAN MAHASISWA BERMASALAH MENGGUNAKAN METODE AHP - Agus Kristianto (Universitas Sahid Surakarta, 2017)
Selection the type and weight of student violations rather hard done by the College, sometimes a student has a good performance in terms of the lecture but on theother side is less good behavior or attitude compared to other students and vice versa. Assessment methods should be developed to make the selection and evaluation of the students indicated particularly problematic, in order to do the evaluation and handling more structured and transparent so that the students can understand the basic evaluation of College and was treated fairly. In this study, a Decision Support System (DSS) which resulted in a system for support in decision-making to determine objectively the student in question and it concerns also specific guidance. DSS created using decision table, the criteria used is the index value achievement, long study, long leave of absence (inactive), the number of absences, payments of fees, alcohol, drugs and fighting. The system can display decision tables according to existing theory and display the list of problem students in accordance with the conditions in the decision table. In tests, the system is quite effective in the calculation that uses looping and branching and has been tested using white box.